Seating of the Femoral Stem after Washing versus Un-washing the Femoral Canal in Cementless Short Stem Hip Arthroplasty - Tippimanchai, Thanut; Suksathien, Yingyong; Sueajui, Jithayut (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: This study aimed to evaluate the effect of washing the femoral canal on the seating of the short femoral stem in cementless short-stem hip arthroplasty. Methods: This single-center randomized controlled trial included 50 patients divided into unwashed and washed groups. All patients underwent cementless short-stem hip arthroplasty with the Metha® short-stem. The primary outcome measured was the discrepancy between the final rasp and implanted stem, with a mismatch of >2 mm considered clinically significant. Secondary outcomes included intraoperative factors associated with a significant mismatch. Univariate logistic regression analysis was used to identify factors related to a clinically significant mismatch between the final rasp and implant. The subsidence and revision were recorded at 4 years follow-up. Results: The study found that 44% of the cases in the unwashed group had a clinically significant mismatch, compared with 8% in the washed group (P=0.001). The mean discrepancy was 2.4 mm in the unwashed group and 1.2 mm in the washed group (P<0.001). Univariate regression analysis indicated that not washing the canal was associated with a higher rate of significant mismatches (odds ratio [OR]=9.05, P=0.009). No cases of stem subsidence or revision were observed at 4 years follow-up in either group. Conclusions: Washing the femoral canal with saline significantly reduced the discrepancy between the final rasp and the implant in cementless short-stem hip arthroplasty, potentially improving surgical outcomes and reducing leg length discrepancies.